Electrical Properties of CSS Deposited CdTe Thin Films for Solar Cell Applications - Das N.K.; Razi S.A.; Rahman K.S.; Matin M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cadmium sulfide; Cadmium telluride; Deposition; Electric properties; Hall effect; Hole concentration; Hole mobility; II-VI semiconductors; Inert gases; Robotics; Semiconducting films; Solar cells; Sublimation; Thin film solar cells; CdTe; Close spaced sublimation; Deposition temperatures; Hall effect measurement; N-type conductivity; Optimum temperature; Solar-cell applications; Substrate temperature; Thin films